2013
DOI: 10.1017/jfm.2013.413
|View full text |Cite
|
Sign up to set email alerts
|

Inertial instability of intense stratified anticyclones. Part 2. Laboratory experiments

Abstract: International audienceLarge-scale laboratory experiments were performed on the Coriolis rotating platform to study the stability of intense vortices in a thin stratified layer. A linear salt stratification was set in the upper layer on top of a thick barotropic layer, and a cylinder was towed in the upper layer to produce shallow cyclones and anticyclones of similar size and intensity. We focus our investigations on submesoscale eddies, where the radius is smaller than the baroclinic deformation radius. Towing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 33 publications
(82 reference statements)
5
26
1
Order By: Relevance
“…This is in agreement with the two-dimensional nonrotating flow in the limit of large Reynolds number, for which the Strouhal number, S t = f s D/U 0 = D/L e 0.2 − 0.24, at large Reynolds numbers [Wen and Lin, 2001]. Both experimental [Boyer and Kmetz, 1983;Stegner et al, 2005;Teinturier et al, 2010;Lazar et al, 2013b] and numerical studies [Heywood et al, 1996;Perret et al, 2006a] confirm this result in a deepwater configuration when the bottom friction is negligible. Hence, a quasi-geostrophic wake will have the same pattern as the standard nonrotating Karman street even if the separation and the vortex shedding occur at higher critical Reynolds numbers [Boyer and Kmetz, 1983;Boyer et al, 1984].…”
Section: Quasi-geostrophic Wakesupporting
confidence: 86%
See 2 more Smart Citations
“…This is in agreement with the two-dimensional nonrotating flow in the limit of large Reynolds number, for which the Strouhal number, S t = f s D/U 0 = D/L e 0.2 − 0.24, at large Reynolds numbers [Wen and Lin, 2001]. Both experimental [Boyer and Kmetz, 1983;Stegner et al, 2005;Teinturier et al, 2010;Lazar et al, 2013b] and numerical studies [Heywood et al, 1996;Perret et al, 2006a] confirm this result in a deepwater configuration when the bottom friction is negligible. Hence, a quasi-geostrophic wake will have the same pattern as the standard nonrotating Karman street even if the separation and the vortex shedding occur at higher critical Reynolds numbers [Boyer and Kmetz, 1983;Boyer et al, 1984].…”
Section: Quasi-geostrophic Wakesupporting
confidence: 86%
“…However, it could be easier to perform PIV (particle image velocimetry) measurements with a top-view camera if the fluid layer is at rest, on the rotating turntable, and the cylinder is translated at a constant speed (Figure 14.2b). Such configurations with high-resolution PIV measurements were used in recent experiments [Stegner et al, 2005;Perret et al, 2006b;Teinturier et al, 2010;Lazar et al, 2013b], especially when the rotating fluid layer is stratified ( Figure 14.2c).…”
Section: Idealized Laboratory Setups For Oceanic Island Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…They note that solving numerically for the linear stability of baroclinic vortices with continuous stratification is much more challenging, as the problem becomes nonseparable in the vertical and radial directions. The results here indicate a further complication compared to the large body of research of vortex stability (e.g., Kloosterziel and van Heijst 1991;Billant and Gallaire 2005;Lahaye and Zeitlin 2015;Lazar et al 2013;Smyth and McWilliams 1998) in that the stability of the vortices varies in the azimuthal direction. This variation occurs because of the opposing effect of the Ekman buoyancy flux on either side of a vortex.…”
Section: Discussionmentioning
confidence: 50%
“…Both theoretical predictions [31,32] and laboratory experiments [33,34] have shown that anticyclonic vortices are more susceptible to inertial instability. This has been used to explain the preponderance of cyclonic submesoscale eddies observed at the ocean surface [35].…”
Section: Introductionmentioning
confidence: 99%